PENINGKATAN PERTUMBUHAN DAN ANTOSIANIN PADI HITAM (Oryza sativa ‘cempo ireng’) DENGAN PUPUK KANDANG - Dewi, M.Sc.St, Dr. Kumala (Agrin, 2019)
Nowdays people tend to consume good healthy diets such as black rice. Black rice contain anthocyanin that acts as antioxidant. High demand of black rice in the market need to synchronize with high production that can be fulfil by fertilizer application. This research conducted to evaluated growth and yield of black rice ‘Cempo Ireng’ by cytokinin and manure application. Research was start in November 2015-Mei 2016 at Sangihe District. The treatment was arranged by dosage of manure 0, 5, 10, 15 ton ha-1 and incubated for two week. The results of this study showed that manure can affect the growth and yield of black rice.